Block-Based Development of a Mobile Application in Basic Electrical Concept for Diploma in Electrical Engineering Student - Morsin, Marriatyi; Ali, Halizah (Journal of Electronic Voltage and Application, 2021)
Electrical Technology is one of the main courses for Diploma in Electrical Engineering students in Politeknik Malaysia. The subject has been delivered conventionally; however, due to the Covid-19 pandemic, relatively it has changed the landscape in delivery method. Regarding this problem, an innovation by using an online learning application is a must. Online study requires students to get other supplementary aids to enhance their understanding of subjects. The supplementary aids should be easy for students to access and can be used anytime and anywhere. This paper presents the block-based programming language used in App Inventor to make the creation of mobile apps for basic electrical concepts for electrical engineering students in Politeknik. Such an app is used to convert the resistance color codes to resistance values and calculate the total resistance in the circuit. Results showed that this mobile application is useful for students to solve basic electrical concept problems. It is proved that this app is user-friendly and attractive.